Using Micro-Learning to Enhance Knowledge and Skills of Airway Management in Nurse Anesthesia Students: An Interventional Study - Masoumeh Albooghobeish; Alireza Ghalandeh; Ali Khalafi; Mohammad Hosein Haghighizadeh (Archives of Anesthesia and Critical Care)
Background: As a subfield of E-Learning, Micro-Learning provides asynchronous instruction to reduce mental strain and boost understanding by delivering educational content in bite-sized, concise learning modules. This study aimed to investigate the effect of Micro-Learning on the airway management knowledge and skills of nurse anesthesia students. Methods: This Non-Randomized Controlled study, employing a Pre-test-Post-test design, included 52 nurse anesthesia students in Iran. Participants were first assessed with a Pre-test, and then assigned to either the M-L M (n=26) or T M (n=26) groups. Over three weeks, the M-L M group received Micro-Learning-based materials through social media, while the T M group received traditional face-to-face instruction. The intervention focused on airway management during peri-induction of general anesthesia. Then, the first and second Post-tests were given to assess the acquisition and retention of knowledge and skills, using a researcher-made instrument called AMAI-NA. Results: Based on within-group comparisons, in both M-L M and T M groups mean scores of both Knowledge and Skills significantly increased from the Pre-test to 1st Post-test, then declined from 1st Post-test to 2nd Post-test. Yet, 2nd Post-test mean scores remained significantly higher than the Pre-test for both groups. Based on Inter-group comparisons, despite the absence of a statistically significant difference in Pre-test mean scores between the two groups, the mean scores for Knowledge and Skills of the M-L M group were significantly higher than those of the T M group in 1st and 2nd Post-tests. Furthermore, the M-L M group exhibited a greater increase in mean scores from the Pre-test to 1st and 2nd Post-tests compared to the T M group, as well as a lesser decrease from 1st Post-test to 2nd Post-test. Conclusion: This study demonstrated that Micro-Learning significantly enhanced the acquisition and retention of knowledge and skills related to airway management, compared to the traditional method.